Self‐Assembly of Oriented Antibody‐Decorated Metal–Organic Framework Nanocrystals for Active‐Targeting Applications (Adv. Mater. 21/2022). Issue 21 (26th May 2022) - Alt, Karen; Carraro, Francesco; Jap, Edwina; Linares‐Moreau, Mercedes; Riccò, Raffaele; Righetto, Marcello; Bogar, Marco; Amenitsch, Heinz; Hashad, Rania A.; Doonan, Christian; Hagemeyer, Christoph E.; Falcaro, Paolo
Abstract : Antibody‐Decorated Nanocrystals Antibody‐targeted nanoparticles are increasingly important for precision medicine. However, it is still challenging to attach antibodies to nanomaterials in a controlled way. In article number 2106607, Karen Alt, Christoph E. Hagemeyer, Paolo Falcaro, and co‐workers demonstrate a one‐step synthesis of oriented antibody‐decorated nanocrystals (in blue). The crystallization only occurs around the antibody's constant region (in red‐yellow) leaving the binding regions free for target engagement. This work has broad potential for diagnostic imaging and targeted drug delivery.